Trabalho em Função do Género, Trabalho Migratório: Reformar os Regimos do Açúcar em Xinavane, Moçambique - Lazzarini, Alicia Hayashi (Desafios para Moçambique 2020, 2020)
O açúcar tem desempenhado um papel fundamental e controverso em Moçambique. Desde 1996, o Governo moçambicano e a iniciativa privada aproveitaram-se da ideia de que a África é a «última fronteira» do investimento (Diop et al., 2015; The Economist, 2013; Sizemore, 2012) para reinvestir numa economia devastada pela guerra civil e «reabilitá-la». Com um crescimento de sete por cento e, nos últimos anos, uma das taxas mais elevadas de investimento estrangeiro em África, Moçambique tem sido apresentado como um país posicionado para um crescimento explosivo. O açúcar tem desempenhado um papel crucial na transformação do presumível potencial da paisagem moçambicana em produtividade e na restauração da capacidade da nação para competir em mercados globais. A Açucareira de Xinavane tem sido o exemplo notável deste esforço de reabilitação. Antigamente conhecido como uma propriedade colonial menor, o actual empreendimento conjunto entre o Governo de Moçambique e a empresa sul-africana Tongaat Hulett tornou a Açucareira a maior plantação de açúcar do País. Entre 2005 e 2013, a área de cana-de-açúcar cultivada triplicou de 6000 para mais de 17 000 hectares (ha), com um aumento correspondente na produção de cana-de-açúcar, de 500 000 para 1,5 milhões de toneladas. A nova abordagem da produção de Xinavane enfatiza as técnicas de quantificação, cálculo e gestão originárias dos institutos de pesquisa de açúcar da África do Sul. Representantes da empresa e da indústria nacional descrevem a reabilitação da fábrica como a implementação directa da prática industrial padrão, apesar de enfrentar um contexto de «desenvolvimento» desafiador. Nas descrições do Governo e da indústria, o açúcar fornecerá empregos, infra- -estruturas necessárias e centros rurais com bancos, escolas e hospitais que beneficiarão todos os moçambicanos. Com este objectivo, foram levados a Xinavane peritos industriais regionais para formar gestores moçambicanos, supervisionar o restabelecimento e o crescimento da indústria e, finalmente, tornar possível o «progresso» económico e social de um país emergente de uma situação de conflito e, assim, construir uma economia capitalista competitiva. O presente artigo levanta questões sobre as tensões no seio desta abordagem tecnicamente estruturada. Analisa sobretudo as estratégias emergentes de gestão do trabalho, e identifica a forma como as «novas» práticas gerem uma força de trabalho grande e anteriormente indisciplinada. Esta gestão tem sido realizada através da divisão geográfica e de género, que não só reforça as baixas valorizações sociais e materiais da vida e do trabalho rural moçambicano, mas também restabelece um regime de trabalho profundamente associado à violência do passado colonial. Ao interrogar a dinâmica material e discursiva da «ciência da indústria» e da «tecnologia» na prática, ponho em causa os alegados impactos modernizadores desta abordagem «nova» no Moçambique pós-colonial.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; employment / emprego; gender / género

Gender Roles, Relationships and Social Equity in Post-Harvest Management in Mozambique - FANRPAN (ood, Agriculture and Natural Resources Policy Analysis Network, 2018)
Key Recommendations: 1. Gender and other general policies in the agricultural sector should be revised to reflect clear priorities for lowering post-harvest losses (PHL). 2. Crop scientists should be trained and crop-specific PHM research infrastructure should be developed so that PHM can be included as a research component for all crops. 3. Academic and research units should be located in the field, close to the farmers, so that researchers and/or university students are closer to the beneficiaries. 4. PHM programs, projects, and activities must include information and technology development and dissemination relevant to the end-users, including women, children, the youth, and poorer farmers. 5. PHL should be reduced by increasing access to carts/wheelbarrows and their respective repair kits and to draught animals, repairing critical sections of rural roads, and increasing farmers’ access to bags/sacks that are not infested and in good condition. 6. Reduce PHL along the value chain from farm to plate by extending innovations to some of the socially perceived “female-roles” of PHM. 7. Development and dissemination of PHM innovations must also be part of policies, strategies, and practices to promote a better workload distribution by increasing male participation in labourdemanding PHM activities culturally assigned to women. 8. Since women in polygamous marriages and single mothers are easier to work with when it comes to promoting investment in PHM improvements due to their decision-making power in the households, they should be given priority in work plans. 9. Prioritize female farmers in PHM capacity-building initiatives, because they are the ones who deal with most of the PHM activities. 10. Local tools manufacturers should benefit from incentives to lower the cost for the development of manufacturing, processing, and packaging equipment to make them accessible to women and the poor.
Keywords: G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; gender / género

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year One - Tvedten, Inge (ORGUT Consulting AB, 2012)
he Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. This is the Annual Report for Year One of the Reality Checks and aims at summarising the conclusions based on the findings from the field sub-report from each study location.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; poverty / pobreza